Continental Shelf Submissions: an Updated Record - Macnab, Ron (The International Hydrographic Review, 2007)
To date, nine coastal states have presented a total of eight submissions for continental shelf extensions beyond their 200 nautical mile limits. This paper summarizes the scopes of those submissions and the stages they have attained in their examinations by the Commission on the Limits of the Continental Shelf. The paper also identifies the members of the three Commissions that have been elected since 1997, and of the seven subcommissions that have been established since 2001 for the purpose of reviewing individual submissions.